PENGARUH KEPEMIMPINAN TRANSFORMASIONAL TERHADAP LOYALITAS KERJA KARYAWAN PADA PT. JASA RAHARJA CABANG PEKANBARU - Rianopita Ridito; Kasmiruddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This research was conductedatthe PT Jasa Raharja Pekanbaru. The problem in this research is how toinfluencethe transformational leadership to loyalty working at the PT Jasa Raharja Pekanbaru. The purposeofthis research wastodetermine the effectof transformational leadership to loyalty working at the PT Jasa Raharja Pekanbaru.Qualitative data obtained from filling the questionnaire by respondents transformed into quantitative data to give a score to each answer choice Likert scale. The data analysis technique used is descriptive analysis and quantitative analysis as well as some theories on transformational leadership and employee loyalty. Total population is all employees of the PT. Jasa Raharja Pekanbaru amounted to 39 people. The sampling is done by census method (sampling saturated). To collect data and information in this research technique used is the technique of questionnaire. Source of data used are primary and secondary data. Primary data is data obtained from questionnaires while secondary data obtained from the document PT. Jasa Raharja Pekanbaru. Based on hypothetical calculations known t count equal to 3.952 while t tabel with α of 0.05 df of 39 known value table = 2.030 then thus: t count> t table (3.952> 2.023), then this means that is the influence of transformational leadership on employee loyalty in PT Jasa Raharja Pekanbaru.Keywords: transformational leadership, loyalty of employee performance.